The processing of raising and nominal control: an eye-tracking study - Sturt, Patrick; Kwon, Nayoung (Frontiers in Psychology, 2015)
According to some views of sentence processing, the memory retrieval processes involved in dependency formation may differ as a function of the type of dependency involved. For example, using closely matched materials in a single experiment Dillon et al (2013) found evidence for retrieval interference in subject-verb agreement, but not in reflexive-antecedent agreement. We report four eye-tracking experiments that examine examine reflexive-antecedent dependencies, combined with raising (e.g. ``John seemed to Tom to be kind to himself...''), or nominal control (e.g. ``John’s agreement with Tom to be kind to himself...''). We hypothesized that dependencies involving raising would (a) be processed more quickly, and (b) be less subject to retrieval interference, relative to those involving nominal control. This is due to the fact that the interpretation of raising is structurally constrained, while the interpretation of nominal control depends crucially on lexical properties of the control nominal. The results showed evidence of interference when the reflexive-antecedent dependency was mediated by raising or nominal control, but very little evidence that could be interpreted in terms of interference for direct reflexive-antecedent dependencies that did not involve raising or control. However, there was no evidence either for greater interference, or for quicker dependency formation, for raising than for nominal control.